Comparative Effectiveness of Exercise-Based Interventions on Pain and Physical Function in Knee Osteoarthritis: A Narrative Review of Recent Evidence Syntheses - Novin Tri Wahyuni; Ummi Kalsum; Humaryanto Humaryanto; Guspianto Guspianto (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Knee osteoarthritis (KOA) is a leading cause of pain and disability among older adults, with exercise-based therapy widely recommended as first-line management. However, findings vary considerably across intervention types, comparators, and outcome measures. Objective: To synthesize and compare recent high-quality evidence regarding the effectiveness of Pilates, traditional Chinese exercise, and multi-modal physiotherapy on pain and physical function in KOA patients. Methods: A narrative synthesis was conducted using three recent evidence sources: a 2025 meta-analysis of Pilates exercise (11 RCTs, n=476), a 2023 meta-analysis of traditional Chinese exercise (17 RCTs, n=1,174), and the MOA Trial evaluating manual and exercise physiotherapy (n=206). Primary outcomes were pain (VAS, NPRS) and physical function (WOMAC) Results and Discussion: Pilates reduced pain versus no intervention (SMD −1.09; 95% CI −2.04 to −0.14) but showed no significant superiority over conventional exercise. Traditional Chinese exercise improved WOMAC pain, stiffness, and function compared with controls, with Tai Chi demonstrating the most consistent benefit. In the MOA Trial, manual physiotherapy produced the greatest WOMAC reduction (−28.5 points; 95% CI −47.8 to −9.2) Conclusion: All three modalities provided modest benefits, though evidence certainty ranged from very low to moderate with substantial heterogeneity. Individualized exercise prescription based on patient preference and access to supervised therapy is recommended over a single universal approach